Comparative microstructures and mechanical properties of mortar incorporating wood fiber waste from various curing conditions - Kittipong Kunchariyakun; Suthatip Sinyoung; Puangrat Kajitvichyanukul (Case Studies in Construction Materials, 2022)
This research investigated the effect of curing conditions on properties of mortar incorporating wood fiber waste (WFW). Normal curing, low heat curing (70 °C) and autoclave curing were compared, while the WFW was added 0–5% by weight of ordinary Portland cement. The increasing percentages of WFW reduced the dry density, compressive and flexural strengths, approximately 4–13%, 10–70% and 3–65%, respectively, under all curing conditions. The application of autoclave curing has relatively low values of flexural-compressive strength ratio compared to normal curing and low heat curing. The highest flexural-compressive strength ratio was the mortar incorporating WFW 5% by weight under normal curing at 28 days. The width of the interfacial transition zone between WFW and mortar at 28 days normal curing was relatively low (44.72 ± 14.63 µm) compared to autoclave curing (23.84 ± 8.90 µm). Microstructure analysis revealed that autoclave curing leads to the hydration products being crystalline, while hydration products can be developed during the curing process. Results from this work can benefit in selecting the curing conditions for the WFW mortar.